L1CAM expression as a predictor of platinum response in high‐risk endometrial carcinoma. Issue 4 (10th May 2022) - Romani, Chiara; Capoferri, Davide; Reijnen, Casper; Lonardi, Silvia; Ravaggi, Antonella; Ratti, Martina; Bugatti, Mattia; Zanotti, Laura; Tognon, Germana; Sartori, Enrico; Odicino, Franco; Calza, Stefano; et al.
Abstract: For high‐risk endometrial cancer (EC) patients, adjuvant chemotherapy is recommended to improve outcome. Yet, predictive biomarkers for response to platinum‐based chemotherapy (Pt‐aCT) are currently lacking. We tested expression of L1 cell‐adhesion molecule (L1CAM), a well‐recognised marker of poor prognosis in EC, in tumour samples from high‐risk EC patients, to explore its role as a predictive marker of Pt‐aCT response. L1CAM expression was determined using RT‐qPCR and immunohistochemistry in a cohort of high‐risk EC patients treated with Pt‐aCT and validated in a multicentric independent cohort. The association between L1CAM and clinicopathologic features and L1CAM additive value in predicting platinum response were determined. The effect of L1CAM gene silencing on response to carboplatin was functionally tested on primary L1CAM‐expressing cells. Increased L1CAM expression at both genetic and protein level correlated with high‐grade, non‐endometrioid histology and poor response to platinum treatment. A predictive model adding L1CAM to prognostic clinical variables significantly improved platinum response prediction (C‐index 78.1%, P = .012). In multivariate survival analysis, L1CAM expression was significantly associated with poor outcome (HR: 2.03, P = .019), potentially through an indirect effect, mediated by its influence on response to chemotherapy. In vitro, inhibition of L1CAM significantly increased cell sensitivity to carboplatin, supporting a mechanistic link between L1CAM expression and response to platinum in EC cells. In conclusion, we have demonstrated the role of L1CAM in the prediction of response to Pt‐aCT in two independent cohorts of high‐risk EC patients. L1CAM is a promising candidate biomarker to optimise decision making in high‐risk patients who are eligible for Pt‐aCT. Abstract : What's new? Endometrial cancer patients with high‐risk disease typically receive adjuvant platinum‐based chemotherapy. So far, no biomarkers can predict platinum chemotherapy response, one of the most important factors affecting prognosis. Here, the authors report their findings that overexpression of the transmembrane protein L1CAM predicts poor response to platinum‐based chemotherapy in high‐risk endometrial cancer patients. Inhibiting L1CAM sensitised cultured cells to carboplatin, supporting a mechanistic link between L1CAM expression and response to platinum therapy. Assessment of L1CAM could therefore improve the treatment selection process, allowing patients who are less likely to benefit from platinum to pursue alternative treatment options.